2009
DOI: 10.1007/s11135-009-9285-0
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive interviewing and factor-analytic techniques: a mixed method approach to validity of survey items measuring national identity

Abstract: Multi-method approach, Cognitive interviewing, Exploratory and confirmatory analysis, National identity, Validity, ISSP,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…First, respondents in both countries had issues with the word “pride” (Latcheva 2011; Meitinger and Behr 2016). Second, German respondents struggled with the high complexity of terms, such as “social security system” (Meitinger and Behr 2016).…”
Section: The Concepts Of Constructive Patriotism and Nationalismmentioning
confidence: 99%
“…First, respondents in both countries had issues with the word “pride” (Latcheva 2011; Meitinger and Behr 2016). Second, German respondents struggled with the high complexity of terms, such as “social security system” (Meitinger and Behr 2016).…”
Section: The Concepts Of Constructive Patriotism and Nationalismmentioning
confidence: 99%
“…It is not clear that the form of national identification found in such a country as Canada is directly comparable with that found in Japan. For example, a study in Austria indicates that respondents do not understand the question items designed to measure national identification in the ISSP National Identity module (Latcheva ). Another study has shown how the meanings of civic and ethnic national identities vary across countries (Reskens and Hooghe ).…”
Section: Measurementsmentioning
confidence: 99%
“…However, in comparative research, the issue of comparability across countries must be addressed (Davidov et al, 2014a ). Respondents in different countries may understand survey questions in various ways (Latcheva, 2011 ; Braun et al, 2013 ) or respond in systematically different ways to the same questions (Harkness et al, 2010 ). This may lead to biased means, factor loadings and regression coefficients.…”
mentioning
confidence: 99%